Sustained virological response to treatment of chronic hepatitis C with peginterferon alfa and ribavirin - Junior André da Rosa; Carine Raquel Blatt; Kaite Cristiane Peres; Bernd Heinrich Storb; Rochele Silva; Mareni Rocha Farias (Universidade de São Paulo, 2012)
This study aimed to evaluate the rate of sustained virological response (SVR) and the clinical and treatment characteristics of patients with chronic hepatitis C (CHC). A retrospective uncontrolled cohort study was conducted among patients who received treatment for CHC between 2005 and 2008 attended at the Center for the Application and Monitoring of Injectable Medications, in Florianopolis, SC, Brazil. The inclusion criteria were: patients over 18 years of age, with a confirmed diagnosis of chronic hepatitis C according to Brazilian guidelines, treated with PEG-IFN alfa-2a or 2b associated with RBV. A total of 188 patients were included in the study: 70% men, 59% genotype 1, 27% coinfected with HIV, 31% with cirrhosis. The SVR rate, calculated by probability theory, was determined as 26% (max=57.4% and min=12.8%) and the intention to treat was 12.8%. Associations between Sustained Virological Response (SVR) and the variables sex (p=0.017), age (p=0.003), genotype (p=0.648) and cirrhosis (p=0.275), were determined in the bivariate analysis and only sex and age were significantly associated with SVR. The SVR rate was considered low, which can be partially explained by patients' unfavorable pretreatment characteristics. O objetivo do estudo foi avaliar a taxa de resposta viral sustentada (RVS) e as características clínicas e do tratamento dos pacientes portadores de hepatite C crônica. Realizou-se uma coorte retrospectiva não controlada com recorte temporal dos anos de 2005 a 2008, dos pacientes atendidos no Polo de Aplicação e Monitoramento de Medicamentos Injetáveis, em Florianópolis, SC. Os critérios de inclusão foram: pacientes maiores de 18 anos, com diagnóstico confirmado de hepatite C crônica de acordo com o protocolo brasileiro, tratados com PEG-IFN alfa-2a ou 2b associado a ribavirina. Total de 188 pacientes foi incluído no estudo, 70% homens, 59% genótipo 1, 27% co-infectados com o HIV e 31% apresentando cirrose. A taxa de RVS calculada através da teoria das probabilidades foi de 26% (max=57,4% and min=12,8%) e por intenção de tratamento de 12,8%. Verificou-se a associação da RVS com as variáveis: sexo (p=0,017), idade (p=0,003), genótipo (p=0,648) e presença de cirrose (p=0,275). Somente sexo e idade foram associados significativamente com a RVS. A taxa de RVS foi considerada baixa e, em parte, pode ser explicada pelas características desfavoráveis dos pacientes para a obtenção de RVS.